Tradition or change? Sources of body procurement for the Anatomical Institute of the University of Cologne in the Third Reich. Issue 4 (12th August 2013) - Kaiser, Stephanie
Abstract: While it is known that all German anatomical institutes that have been examined made use of the bodies of victims of the National Socialist (NS) regime for teaching and research between 1933 and 1945, detailed investigations on many institutions are still missing. Among these is the anatomical institute of the University of Cologne. This university was the first university to voluntarily self‐align with the policies of the new regime and was therefore often called a 'model NS university'. In addition, Cologne was the site of a NS special court and a central place for executions. Based on archival sources, this study investigates the interaction between the anatomical institute of the University of Cologne with the NS authorities and the origin of the body supply for dissection and research. The documents reveal that the institute continued to receive bodies from traditional sources like the public morgue and hospitals, but with the beginning of World War II (WWII) an increasing amount of bodies of victims of the NS regime became available. Thus, the anatomical institute of Cologne collaborated and benefited from the policies of the NS regime, especially during WWII, like all other already explored anatomical institutes in Germany to varying degrees.